2021
DOI: 10.3389/fphar.2021.657047
|View full text |Cite
|
Sign up to set email alerts
|

Branched-Chain Amino Acids Catabolism Pathway Regulation Plays a Critical Role in the Improvement of Leukopenia Induced by Cyclophosphamide in 4T1 Tumor-Bearing Mice Treated With Lvjiaobuxue Granule

Abstract: Background: Cyclophosphamide is a common tumor chemotherapy drug used to treat various cancers. However, the resulting immunosuppression leads to leukopenia, which is a serious limiting factor in clinical application. Therefore, the introduction of immunomodulators as adjuvant therapy may help to reduce the hematological side effects of cyclophosphamide. Lvjiaobuxue granule has been widely used in the clinical treatment of gynecological diseases such as anemia and irregular menstruation. Recently, it has been … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 43 publications
1
4
0
Order By: Relevance
“…haematopoietic stem cells and haematopoietic progenitor cells) from producing peripheral blood cells (Liu et al, 2014). Hence, measuring these peripheral blood cells count, directly mirrors the haematopoietic function (Tian et al, 2021). In line with previous studies (El-Naggar et al, 2015;Iqubal et al, 2020;Kameo et al, 2021), CPA administration at 200 mg/kg i.p.…”
Section: Discussionsupporting
confidence: 74%
“…haematopoietic stem cells and haematopoietic progenitor cells) from producing peripheral blood cells (Liu et al, 2014). Hence, measuring these peripheral blood cells count, directly mirrors the haematopoietic function (Tian et al, 2021). In line with previous studies (El-Naggar et al, 2015;Iqubal et al, 2020;Kameo et al, 2021), CPA administration at 200 mg/kg i.p.…”
Section: Discussionsupporting
confidence: 74%
“…Wang et al reported that ginseng protein enhanced the immunoregulation of macrophages (Wang et al, 2018), which improved Alzheimer's disease by activating the BDNF/TrkB signaling pathway and regulating the intestinal microbial diversity (Li et al, 2022). Tian et al reported that Lvjiaobuxue granule could improve the leukopenia induced by CP in 4T1 tumor-bearing mice by regulating the branched-chain amino acid degradation pathway and the levels of Val, Leu, and Ile (Tian et al, 2021). Such proteins or peptides of GE also participate in immune regulation in immunosuppressed mice.…”
Section: Discussionmentioning
confidence: 99%
“…Wilkinson et al reported that reduced BCAA levels inhibited hematopoietic stem cell proliferation and survival in vitro and rendered these cells incapable of sustaining normal physiological activity in vivo [ 54 ]. Likewise, dietary BCAA depletion could lead to a significant decrease in WBC and RBC counts in normal mice [ 55 ]. Because soy and whey protein extracts contain abundant BCAAs [ 56 , 57 ], post-BMT DP supplementation was likely to reverse BCAA-deficits and promote survival and the proliferation of HSC and WBC populations [ 58 , 59 ].…”
Section: Discussionmentioning
confidence: 99%